2012
DOI: 10.1074/jbc.m112.404582
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Pathogen Co-opts Host Plasmin to Resist Killing by Cathelicidin Antimicrobial Peptides

Abstract: Background: Group A Streptococcus (GAS) produces streptokinase (Ska), which activates plasminogen to plasmin while binding the host enzyme to the bacterial surface. Results: Ska-activated plasmin can degrade human cathelicidin LL-37, promoting GAS resistance to the antimicrobial peptide. Conclusion: Ska contributes to GAS innate immune evasion and virulence. Significance: A human pathogen can co-opt the activity of a host protease to subvert peptide-based innate immune defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
3
37
0
1
Order By: Relevance
“…Consistent with previous reports for other GAS strains (30,35), we found that LL-37 had antimicrobial activity for GAS strain 854, with an MIC of 50 M and an MBC of 20 -30 M. The slightly lower concentration of peptide required for killing compared with that for inhibition of growth reflects the different conditions of the two assays: the killing assay was performed under hypotonic conditions that enhance antimicrobial activity. FK-16, which corresponds to the region considered to encompass the core of LL-37 antimicrobial activity (19,20), demonstrated more potent antimicrobial activity than fulllength LL-37, with lower MIC and MBC of 1 and 0.75-1 M, respectively.…”
Section: Mics and Mbcs Of Ll-37 And Itssupporting
confidence: 90%
“…Consistent with previous reports for other GAS strains (30,35), we found that LL-37 had antimicrobial activity for GAS strain 854, with an MIC of 50 M and an MBC of 20 -30 M. The slightly lower concentration of peptide required for killing compared with that for inhibition of growth reflects the different conditions of the two assays: the killing assay was performed under hypotonic conditions that enhance antimicrobial activity. FK-16, which corresponds to the region considered to encompass the core of LL-37 antimicrobial activity (19,20), demonstrated more potent antimicrobial activity than fulllength LL-37, with lower MIC and MBC of 1 and 0.75-1 M, respectively.…”
Section: Mics and Mbcs Of Ll-37 And Itssupporting
confidence: 90%
“…The acquisition of plasmin protease activity on the GAS cell surface plays a key role in GAS pathogenesis (258). GAS surface-bound plasmin activity was recently demonstrated to promote degradation of human cathelicidin LL-37 (259). SIC also binds and inhibits antimicrobial peptide LL-37 (213-215).…”
Section: Resistance To Antimicrobial Peptidesmentioning
confidence: 99%
“…To combat these defenses, GAS has evolved several strategies to evade and counteract the innate phagocyte immune response (2). A significant portion of the global burden of invasive GAS disease is attributable to the prevalent M1T1 clone (4,5), which encodes multiple immune evasion genes, including factors that impede neutrophil recruitment, limit phagocytosis (6,7), resist antimicrobial peptides (8,9), and degrade NETs (10,11). These multiple immune evasion mechanisms may allow GAS to resist the innate immune defenses of the host and allow the bacteria to produce systemic infections, including infections in previously healthy individuals.…”
mentioning
confidence: 99%